RNase H1 Regulates Mitochondrial Transcription and Translation via the Degradation of 7S RNA - Reyes, Aurelio; Rusecka, Joanna; Tońska, Katarzyna; Zeviani, Massimo (Frontiers in Genetics, 2020)
RNase H1 is able to recognize DNA/RNA heteroduplexes and to degrade their RNA component. As a consequence, it has been implicated in different aspects of mtDNA replication such as primer formation, primer removal, and replication termination, and significant differences have been reported between control and mutant RNASEH1 skin fibroblasts from patients. However, neither mtDNA depletion nor the presence of deletions have been described in skin fibroblasts while still presenting signs of mitochondrial dysfunction (lower mitochondrial membrane potential, reduced oxygen consumption, slow growth in galactose). Here, we show that RNase H1 has an effect on mtDNA transcripts, most likely through the regulation of 7S RNA and other R-loops. The observed effect on both mitochondrial mRNAs and 16S rRNA results in decreased mitochondrial translation and subsequently mitochondrial dysfunction in cells carrying mutations in RNASEH1.